2008
DOI: 10.1177/1753465808094971
|View full text |Cite
|
Sign up to set email alerts
|

Review: Oxidant—antioxidant imbalance in asthma: scientific evidence, epidemiological data and possible therapeutic options

Abstract: Prevalence of asthma has increased considerably in recent decades throughout the world especially in developed countries. Airway inflammation is thought to be prime cause for repeated episodes of airway obstruction in asthmatics. Several studies have shown that reactive oxygen species (ROS) play a key role in initiation as well as amplification of inflammation in asthmatic airways. Excessive ROS production in asthma leads to alteration in key enzymatic as well as nonenzymatic antioxidants such as glutathione, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 168 publications
(216 reference statements)
3
95
1
3
Order By: Relevance
“…Sabe-se que a ativação de células como neutrófilos, eosinófilos, monócitos e macrófagos na resposta inflamatória acontece sob condições oxidativas, resultando em um marcado aumento no consumo de oxigênio e consequente produção de espécies reativas de oxigê-nio, culminando no estresse oxidativo 32,41 . Nesse sentido, a proteção conferida em nossos achados pode ter minimizado o estresse oxidativo tanto na asma não atópica (grupo de pescados) quanto na asma atópica (padrão alimentar).…”
Section: Discussionunclassified
“…Sabe-se que a ativação de células como neutrófilos, eosinófilos, monócitos e macrófagos na resposta inflamatória acontece sob condições oxidativas, resultando em um marcado aumento no consumo de oxigênio e consequente produção de espécies reativas de oxigê-nio, culminando no estresse oxidativo 32,41 . Nesse sentido, a proteção conferida em nossos achados pode ter minimizado o estresse oxidativo tanto na asma não atópica (grupo de pescados) quanto na asma atópica (padrão alimentar).…”
Section: Discussionunclassified
“…4,23,24 Asthma is associated with inflammation and increased responsiveness in airways of the lungs and this involves secretion of broncho-constrictive, pro-inflammatory products, chemo-attractants mediators, cytokines and ROS. 4,25 It is suggested that ROS and oxidative stress in asthmatic airways possibly contribute to inflammatory injury and oxidative damage of proteins. 25 Environmental pollutants and endotoxins from microorganisms have the capacity to prompt neutrophilic airway inflammation thus obstructing the airway and as the lung changes due to over reactivity, this increases oxidative stress and proinflammatory mediators such as IL-6 and C-reactive protein.…”
Section: Inflammation In Asthmamentioning
confidence: 99%
“…4,25 It is suggested that ROS and oxidative stress in asthmatic airways possibly contribute to inflammatory injury and oxidative damage of proteins. 25 Environmental pollutants and endotoxins from microorganisms have the capacity to prompt neutrophilic airway inflammation thus obstructing the airway and as the lung changes due to over reactivity, this increases oxidative stress and proinflammatory mediators such as IL-6 and C-reactive protein. [9][10][11][12] Pro-inflammatory mediators in serum are therefore higher in asthmatics by comparison with healthy individuals (Table 1).…”
Section: Inflammation In Asthmamentioning
confidence: 99%
“…Formation of ROS takes place constantly in every cell during normal metabolic processes (Bast, et al, 2010, Finkel, 2011, Ballaban, et al, 2005, Comhair & Erzyrum, 2010. Cellular sites for production of ROS include mitochondria, microsomes, and enzymes (e.g., xanthine oxidase, P450 monooxygenase, cyclooxygenase, lipoxygenase, indole amine dioxygenase, monoamine oxidase) (Nadeem, et al, 2008). One of the most dangerous forms of PM pollution is diesel exhaust particles.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…NF-E2-related factor 2, a basic leucine zipper transcription factor, involved in induction of the antioxidant element (ARE)-mediated transcriptional response is known to play an important role and binds to the ARE and upregulates the expression of several antioxidant genes in response to a variety of stimuli (Nguyen, et al, 2003). ROS (Nadeem, et al, 2008) can influence airway cells and reproduce many of the pathophysiological features associated with asthma by initiating lipid peroxidation, altering protein structure, enhancing release of arachidonic acid from cell membranes, contracting airway smooth muscle, increasing airway reactivity and airway secretions, increasing vascular permeability, increasing the synthesis and release of chemoattractants, inducing the release of tachykinins and neurokinins, decreasing cholinesterase and neutral endopeptidase activities, and impairing the responsiveness of ß-adrenergic receptors (Barnes, et al, 1998). Asthma attacks and experimental allergen challenge are associated with immediate formation of superoxide that persists throughout the late asthmatic response (Calhoun, et al, 1992).…”
Section: Oxidative Stressmentioning
confidence: 99%